ĪJĀZ DAN IṬNĀB DALAM AL-QUR’AN: ANALISIS BALAGAH DAN HIKMAH PERBEDAANNYA (STUDI ATAS QS. AL-BAQARAH: 120, 145 DAN QS. AR-RA‘D: 37) - Mursalin Mursalin; Andi Miswar; Mohamad Harjum (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
This study departs from the fact that the Qur’an not only conveys theological and legal teachings, but also demonstrates rhetorical beauty through various linguistic styles, particularly ījāz (concise expression) and iṭnāb (elaborative expression). The different use of these two styles in verses with similar themes indicates a contextual and meaningful linguistic strategy. This research aims to analyze the forms, rhetorical functions, and wisdom behind the use of ījāz and iṭnāb in verses sharing thematic similarities, especially in QS. Al-Baqarah verses 120 and 145, as well as QS. Ar-Ra‘d verse 37. This study employs a qualitative method based on library research with a descriptive-analytical approach. The primary data consist of the selected Qur’anic verses, while the secondary data are obtained from classical tafsir works and balāghah literature. The analysis is conducted through the perspective of ‘ilm al-ma‘ānī by considering aspects of context (siyāq) and communicative situation (maqām). The findings reveal that ījāz and iṭnāb are employed proportionally according to contextual demands. QS. Ar-Ra‘d verse 37 tends to employ ījāz due to its concise context, whereas QS. Al-Baqarah verses 120 and 145 utilize iṭnāb to reinforce emphatic meaning. The differences in diction reflect profound rhetorical precision. The implications of this study affirm that the linguistic beauty of the Qur’an is not merely aesthetic, but also functional and contextual in conveying meaning effectively.